Current Developments in Monetary and Financial Law, Vol. 3. (International Monetary Fund, 2005)
The Legal Department and the Institute of the IMF held their eighth biennial seminar for legal advisers of central banks of member countries on May 7-17,2000. The papers presented in this volume are based on presentations made by the seminar participants. The seminar covered a broad range of topics, including activities of the IMF and other international financial institutions, sovereign debt restructuring, the architecture of the international financial system, and money laundering and the financing of terrorism. In addition, participants addressed the role of central banks, payment systems, securities, technology in the financial sector, and monetary arrangements.